2009
DOI: 10.1007/s11661-008-9748-2
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Interfacial Reactions during Hot-Dip Galvanizing of Steel

Abstract: In the modern galvanizing line, as soon as the steel strip enters the aluminum-containing zinc bath, two reactions occur at the strip and the liquid-zinc alloy interface: (1) iron rapidly dissolves from the strip surface, raising the iron concentration in the liquid phase at the strip-liquid interface; and (2) aluminum forms a stable aluminum-iron intermetallic compound layer at the strip-coating interface due to its greater affinity toward iron. The main objective of this study is to develop a simple and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…First, because of the greater affinity of Al to iron than Zn, Fe-Zn brittle phase is suppressed, leading to the formation of a so called inhibition layer, an intermetallic compound of Fe-Al [1,2]. This is indispensable for a workable galvanized product [3,4]. Second, previous works reported that alloy elements in high strength steel, such as Al, Mn, Si, and Cr, will be selectively oxidized under a protective atmosphere of H 2 + N 2 plus trace amount of water vapor, leading to bare spot defects [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…First, because of the greater affinity of Al to iron than Zn, Fe-Zn brittle phase is suppressed, leading to the formation of a so called inhibition layer, an intermetallic compound of Fe-Al [1,2]. This is indispensable for a workable galvanized product [3,4]. Second, previous works reported that alloy elements in high strength steel, such as Al, Mn, Si, and Cr, will be selectively oxidized under a protective atmosphere of H 2 + N 2 plus trace amount of water vapor, leading to bare spot defects [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The specific composition of the as-received S355K2+N steel plate (400x300x10 mm 3 ) and the zinc bath are respectively given in Table 1 and Table 2. The plate was cut in three sheet samples (350x100x10 mm 3 ).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The plate was cut in three sheet samples (350x100x10 mm 3 ). Two samples, A and B, were considered in order to be galvanized according to standard NF ENI ISO 1461, at 450°C with a holding time of 3 min for specimen A and 10 min for specimen B.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the erosion time increases, the iron concentration reaches saturated state in the erosion layer, which results in the rapid interface corrosion reaction and the formation of large amounts of corrosion products. Previous studies also reported that the initial corrosion reaction proceeds very fast when the metal immerses into liquid metal [36][37][38]. The corrosion rate and the time can be estimated by the Eq.…”
Section: Effect Of Fe 2 B Orientation On the Erosion-corrosion Resistmentioning
confidence: 99%